2021
DOI: 10.1002/jcla.23821
|View full text |Cite
|
Sign up to set email alerts
|

tRNAIniCAT inhibits proliferation and promotes apoptosis of laryngeal squamous cell carcinoma cells

Abstract: Background Laryngeal squamous cell carcinoma (LSCC) brings a heavy blow to the patient's voice. Transfer RNA (tRNA) is a common RNA, the roles of tRNAs in LSCC are largely unknown. Methods The tRNA expression profile in LSCC tissues and adjacent normal tissues was measured by a tRNA qRT‐PCR array. The expression level of tRNAIniCAT in LSCC tissues and plasmas was detected by qRT‐PCR. The receiver operating characteristic (ROC) curve was established. tRNAIniCAT was upregulated by a lentivirus vector in the LSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…An independent study generated stably transfected derivatives of a breast carcinoma line in which tRNA-iMet-CAT expression was raised ~1.5-fold; this also stimulated proliferation significantly, as well as decreasing apoptosis [18]. In contrast to these proliferative responses in breast epithelial cells, 2.1-fold overexpression of tRNA-iMet-CAT in a laryngeal squamous cell carcinoma cell line suppressed proliferation in favour of apoptosis [50]. Other studies found no effect of tRNA-iMet-CAT overexpression on the proliferation of human glioma cells [51], mouse melanoma [52] or mouse embryonic fibroblasts [53]; however, it had other oncogenic effects in these systems.…”
Section: Trna-imet and Trna-met Genesmentioning
confidence: 99%
“…An independent study generated stably transfected derivatives of a breast carcinoma line in which tRNA-iMet-CAT expression was raised ~1.5-fold; this also stimulated proliferation significantly, as well as decreasing apoptosis [18]. In contrast to these proliferative responses in breast epithelial cells, 2.1-fold overexpression of tRNA-iMet-CAT in a laryngeal squamous cell carcinoma cell line suppressed proliferation in favour of apoptosis [50]. Other studies found no effect of tRNA-iMet-CAT overexpression on the proliferation of human glioma cells [51], mouse melanoma [52] or mouse embryonic fibroblasts [53]; however, it had other oncogenic effects in these systems.…”
Section: Trna-imet and Trna-met Genesmentioning
confidence: 99%